Sergei A. Ivanov’s Italian Études: to the Problem of Archaeological Reconstructions in the 1800s–1850s - Zhizhina-Hefter, Vera B. (Actual Problems of Theory and History of Art, 2015)
The paper focuses on theoretical and archaeological research undertaken by Sergei A. Ivanov (1822–1877) — a Russian architect and art historian — during his stay in Italy from 1846 till his death. Ivanov did a lot to reconstruct several architectural monuments dating back to Classical antiquity. Compared with his predecessors’ similar attempts, Ivanov’s work was based on meticulous measuring and archaeological study of the ruins. He proposed original interpretation of such reliquiae as the Baths of Caracalla in Rome, and a number of the most significant buildings at Pompeii. Later, after his journey to Greece in 1857–1858, he created reconstructions of several Greek monuments as well. High professional level of Ivanov’s projects and the scope of his work would have made him a name, but his results so far remain underestimated. Although published only partly, they were highly praised by the reviewers, and should be actually referred to as the first Russian works on reconstruction of ancient Greek and Roman architecture based on precise investigation of archaeological material and scrupulous research of original monuments.
Keywords: Sergei A. Ivanov; Baths of Caracalla; architectural reconstruction; Rome; archaeological investigation; Russian Academy of Fine Arts; Russian colony at Rome